Spatiotemporal mapping of vascularization and innervation in the fetal murine intestine. Issue 1 (22nd September 2014) - Hatch, John; Mukouyama, Yoh‐suke
<x xml:space="preserve">Abstract</x> Background: In mice, the intestinal tube develops from the splanchopleure before embryonic day 9.5. Subsequent patterning of nerves and blood vessels is critical for normal digestive function. A hierarchical branching vascular network allows for efficient nutrient absorption, while the complex enteric nervous system regulates intestinal motility as well as secretion, absorption, and blood flow. Despite the well‐recognized significance of these systems, the precise mechanisms by which they develop have not been clearly established in mammals. Results: Using a novel whole‐mount immunohistochemical protocol, we visualize the pattern of intestinal neurovascular development in mice between embryonic day 10.5 and birth. In particular, we focus on the development and remodeling of the enteric vascular plexus, the migration and organization of enteric neural crest‐derived cells, and the integration of peripheral sympathetic nerves with the enteric nervous system. These correlative data lead us to hypothesize a functional interaction between migrating neural crest‐derived cells and endothelial cells of the primary capillary plexus, as well as a subsequent interaction between developing peripheral autonomic nerves and differentiated neural crest‐derived cells. Conclusions: These studies provide useful anatomical data for continuing investigations on the functional mechanisms underlying intestinal organogenesis. Developmental Dynamics 244:56–68, 2015. Published 2014. This article is a U.S. Government work and is in the public domain in the USA